Nutritional Status of Marginalized Adolescent Pregnant Women during their Antenatal Period - Shelley, Farida Easmin; Khatun, Hazera (Ibrahim Cardiac Medical Journal, 2013)
DOI: http://dx.doi.org/10.3329/icmj.v2i1.17415 Ibrahim Cardiac Med J 2012; 2(1): 32-35